The Effect of Socio-Scientific Issue Learning Approach on Problem-Solving Skills, Science Literacy, and Biology Learning Outcomes of Grade XI Students at SMAN 1 Gowa - Uki Cahyana; Firdaus Daud; Andi Asmawati Azis; Yusmina Hala; Faisal Sudrajat (PT. Global Research Collaboration, 2026)
This study investigates the effect of the Socio-Scientific Issue (SSI) learning approach on problem-solving skills, science literacy, and biology learning outcomes of Class XI students at SMAN 1 Gowa. The decline in students' problem-solving skills and science literacy, evidenced by Indonesia's consistently low scores in international assessments such as PISA, calls for innovative instructional approaches. This quasi-experimental study employed a Non-Equivalent Control Group Design with 72 students divided into an experimental class (SSI approach) and a control class (Scientific Approach/5M). Data were collected using essay tests, multiple-choice tests, and structured observation. Analysis included descriptive and inferential statistics using IBM SPSS version 26. Results showed that the SSI class achieved a higher posttest mean in problem-solving skills (81.03 vs. 79.67), science literacy (83.69 vs. 79.22), and cognitive learning outcomes (87.78 vs. 80.14) compared to the control class. Independent Samples T-Test confirmed significant differences for all three variables (p = 0.000 < 0.05). The SSI approach proved more effective than the Scientific Approach in simultaneously developing students’ 21st-century competencies, particularly through contextual engagement with socio-scientific issues related to the human reproductive system.